Estimación de la incapacidad causada por la neumoconiosis - Hurtado, Alberto (1944)
The term pneumoconiosis includes all lung diseases caused by inhalation of dust. Silicosis Among these, due to the action of powdered silica (SiO2) inhaled, is the most important and the qur is in the world a physician-health problem of major proportions. Our country is not immune to this problem. In recent years it has been found, and continues checking the existence of numerous cases of silicosis in the mining areas, where work urgently requires the adoption of preventive measures, with full reasons for the successes that have been provided elsewhere and because it is necessary to retain a human, irreplaceable capital when you take into account the environmental conditions in these areas.